- #1

thomas49th

- 655

- 0

r = i + 2j + 3k

s = 2i - 2j - 5k

t = i - 3j - k

Evaluate:

a)(r.t)s - (s.t)r

b)(r x s) x t.

deduce that (r.t)s - (s.t)r = (r x s) x t

can you prove this relative true for any three vectors

a)(r.t)s - (s.t)r

(r.t)s

well I don't know what s is doing to inside the bracket. I don't think it's the cross product rule.

Anyhow

(r.t) means use dotty dot product

r.t = |r||t|cos(x)

problem uno. I don't know the angle between the vectors.

Am I just being stupid. I thought about possibly trying to get the angle from the cross product, or using some trig identity but I think that'll be a road to nowhere

Hint?

Thanks

Thomas